Development of frozen precooked beef roll - Imperial, Victoria M.
The study was aimed at developing a frozen precooked beef roll product. The best recipe for the filling of beef roll was determined. The modified recipe of hamburger patties from Protein Technologies International with additional spices was found to be the most preferred. This was based on the result of the sensory evaluation test undertaken in the first phase. Standardization and optimization of the developed formulation and process, and laboratory scale production were likewise done. The meat filling was prepared by steaming at 212°C for 25 minutes. Baking time and temperature was determined to be 25 minutes at 375-400 F. The shelf life was estimated to be fifteen days from date of production at -5 to 0 based on the results of the microbiological analysis and sensory evaluation during storage. Product acceptability was determined through market testing using a consumer group of fifty university students. The product was given an acceptability rating of "like moderately" by 46% of the respondents. Product cost was calculated to be P 16.80 per serving, approximately 94 grams each. This price was evaluated to be acceptable by 60% of the consumers.